Treatment of Early-Stage Alzheimer's Disease With CT Scans of the Brain: A Case Report - Jerry M Cuttler; Maryélise S Lamet; Edward J Calabrese (SAGE Publishing, 2022)
We report the case of a patient in Massachusetts with early-stage Alzheimer's disease who was treated with low doses of ionizing radiation to the brain. He requested this treatment after reading about a patient with severe Alzheimer's in Michigan who improved remarkably after receiving 4 CT scans. After his first treatment in April 2016, mental clarity improved. His impaired conversation, reading, and sense of humor were restored, especially his virtuosic clarinet jazz-playing. However, executive function remained deficient. He requested a treatment every 2 weeks, but his neurologist denied this, fearing opposition to this treatment, a diagnostic procedure that used ionizing radiation. Limited recovery was observed after each CT scan, lasting from several weeks to months, depending on the endpoints/behavior and the periodicity. Despite the positive responses, the physician was reluctant to continue beyond 6 due to concerns about adverse effects and disapproval for prescribing them. The patient began hyperbaric oxygen therapy as an alternative. But after 43 treatments, no conclusive benefit was observed. The patient died in September 2020 at age 77. This experience suggests CT scans may have value in treating Alzheimer's patients and restoring, at least temporarily, important aspects of normal life activities. Such observations need testing and validation.